1992
DOI: 10.1136/bmj.305.6861.1068
|View full text |Cite
|
Sign up to set email alerts
|

Electronic communication between providers of primary and secondary care.

Abstract: New technologies are now emerging that have Objective-To study the effects of the introduction considerable potential for improving communication.of electronic data interchange between primary and One such technology is electronic data interchange, secondary care providers on speed of communi-defined as "standard electronic messages conveyed cation, efficiency of data handling, and satisfaction from one computer to another without mdnual interof general practitioners with communication.vention. "' In the Nethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 5 publications
1
52
0
2
Order By: Relevance
“…An expanding body of evidence has demonstrated that improving continuity of care, including communication strategies between clinicians, is feasible, appreciated, and associated with improved patient outcomes. [2][3][4][5][6][7][8][9] Accordingly, understanding transfer errors between outpatient and inpatient settings can help in developing methods of intervention and, consequently, improved patient care. [10][11][12][13][14] Complex hospitalized patients may be particularly vulnerable to communication failures between providers.…”
Section: Introductionmentioning
confidence: 99%
“…An expanding body of evidence has demonstrated that improving continuity of care, including communication strategies between clinicians, is feasible, appreciated, and associated with improved patient outcomes. [2][3][4][5][6][7][8][9] Accordingly, understanding transfer errors between outpatient and inpatient settings can help in developing methods of intervention and, consequently, improved patient care. [10][11][12][13][14] Complex hospitalized patients may be particularly vulnerable to communication failures between providers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, rapid communication of hospital discharge information using electronic data transfer mechanisms has been shown to be beneficial for general practitioners. 21 Hospital discharge summaries have long been identified as a weak point between primary care and hospitals, both because of the tardiness of their arrival, and the quality of the information they contain. Discharge summaries arrive by a variety of means including the post, fax and e-mail.…”
Section: Communication and Primary Carementioning
confidence: 99%
“…Electronic communication was identified as useful at an early stage. 14 Although it is well adopted in some locations, 15 electronic communication with other health personnel and patients is not yet fully implemented in all parts of Norway. Information needs of rural physicians have been described, but not fully realised on an electronic platform.…”
Section: Introductionmentioning
confidence: 99%